2012
DOI: 10.1377/hlthaff.2011.1009
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Were Lifestyle Interventions In Real-World Settings That Were Modeled On The Diabetes Prevention Program?

Abstract: We conducted a systematic review and meta-analysis of twenty-eight US-based studies applying the findings of the Diabetes Prevention Program, a clinical trial that tested the effects of a lifestyle intervention for people at high risk for diabetes, in real-world settings. The average weight change at twelve months after the intervention was a loss of about 4 percent from participants' baseline weight. Change in weight was similar regardless of whether the intervention was delivered by clinically trained profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
499
4
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 524 publications
(546 citation statements)
references
References 45 publications
37
499
4
6
Order By: Relevance
“…18 Change in weight was similar regardless of whether the intervention was delivered by medical and allied health professional or lay community personnel. 17 The number of core sessions attended was strongly correlated with the number of core sessions offered. There was a dose-response association between the number of sessions and amount of weight loss, such that there was a 1% greater weight loss for every four sessions attended.…”
Section: Evidence For Lifestyle Change Prevention Programsmentioning
confidence: 98%
See 3 more Smart Citations
“…18 Change in weight was similar regardless of whether the intervention was delivered by medical and allied health professional or lay community personnel. 17 The number of core sessions attended was strongly correlated with the number of core sessions offered. There was a dose-response association between the number of sessions and amount of weight loss, such that there was a 1% greater weight loss for every four sessions attended.…”
Section: Evidence For Lifestyle Change Prevention Programsmentioning
confidence: 98%
“…Ali and colleagues 17 conducted a systematic review and meta-analysis of 28 U.S.-based studies that adapted the DPP lifestyle intervention in real-world settings at lower cost. 17 Because the DPP study established that weight loss was the single most important factor in reducing type 2 diabetes incidence, Ali et al examined the weight loss achieved in these translation studies. They also examined program characteristics that influence weight loss and cost, including number of core sessions and type of intervention staff.…”
Section: Evidence For Lifestyle Change Prevention Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20]. In a recent study examining translated DPP lifestyle interventions in real-world settings, of the 28 studies examined, over 70 % of participants were female [24]. Among other evidence, a systematic review evaluating major commercial weight loss programs in the USA found that the vast majority of participants were women, upwards of 70 % in most cases [25].…”
Section: Introductionmentioning
confidence: 99%